The role of lay people in religious education. The competency of correlation of the religious education teacher - Tibor Reimer (Polonia Sacra)
The quality of religious education in schools is primarily a matter of the quality of the religious education teachers. In this paper we want to explore different professional perspectives on the acquired competences of the religious education teacher and we want to focus our attention on his specific competency of correlation to linking faith and the life of pupils, Church and school, and Church and society. Therefore, we understand the religious education teacher as a “tightrope walker” who is able to maintain a balance between these different environments.